2017
DOI: 10.18632/oncotarget.15969
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 overexpression in mesenchymal stromal cells from JAK2+ myeloproliferative neoplasms: a new therapeutic target?

Abstract: Histone deacetylases (HDACs) are involved in epigenetic modulation and their aberrant expression has been demonstrated in myeloproliferative neoplasms (MPN). HDAC8 inhibition has been shown to inhibit JAK2/STAT5 signaling in hematopoietic cells from MPN. Nevertheless, the role of HDAC8 expression in bone marrow-mesenchymal stromal cells (BM-MSC) has not been assessed. In the current work we describe that HDAC8 is significantly over-expressed in MSC from in JAK-2 positive MPN compared to those from healthy-dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Because of their role in gene transcription, they have the ability to increase the expression of growth-promoting factors and decrease the expression of tumor suppressors . Recently, HDACs have been found to have other nonhistone substrates. For instance, the knockdown of overexpressed HDAC2 in colorectal cells resulted in the upregulation of the cyclin-dependent kinase inhibitor, p21, independent of p53, supporting the hypothesis that HDAC2 is involved in carcinogenesis . Moreover, numerous studies have demonstrated increased HDAC levels in several cancers compared to normal tissues. , …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because of their role in gene transcription, they have the ability to increase the expression of growth-promoting factors and decrease the expression of tumor suppressors . Recently, HDACs have been found to have other nonhistone substrates. For instance, the knockdown of overexpressed HDAC2 in colorectal cells resulted in the upregulation of the cyclin-dependent kinase inhibitor, p21, independent of p53, supporting the hypothesis that HDAC2 is involved in carcinogenesis . Moreover, numerous studies have demonstrated increased HDAC levels in several cancers compared to normal tissues. , …”
Section: Introductionmentioning
confidence: 97%
“…The United States Food and Drug Administration (FDA) has approved four pan-HDAC inhibitors to date: vorinostat (SAHA), romidepsin (FK228), belinostat (PXD101), and panobinostat (LBH-589) . Pan-HDAC inhibition profiles are associated with adverse side effects such as diarrhea, thrombocytopenia, anemia, and cardiac toxicity. ,,,, Mouse models have highlighted that the selective knockdown of HDAC enzymes can improve therapeutic outcomes, whereas the knockdown of other HDACs results in lethal side effects. For instance, the knockdown studies of HDAC6 and HDAC8 have resulted in an impediment of tumor growth, , whereas the embryonic disruption of specific HDACs (including 1, 2, 3, and 7) in mouse models is associated with lethal outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…PCI-34051 and NCC-149 were among the first HDAC isozyme-selective inhibitors discovered [16][17][18] . These two aromatic hydroxamate derivatives show high selectivity for human HDAC8 (hHDAC8), an HDAC isozyme that has been shown to be overexpressed in several cancers [19][20][21] and whose mutations can lead to the Cornelia de Lange syndrome [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are few reports regarding the possibility to target MSCs to hamper cancer progression. However, recently Ramos et al (2017) reported that the inhibition of Histone deacetylases 8 in MSCs derived from myeloproliferative neoplasms selectively decreases their hematopoietic-supporting ability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%